Experimental-numerical methodology for the manufacturing of cranial prosthesis via laser forming. Issue 5 (September 2016) - Cook, Felipe; Celentano, Diego; Ramos-Grez, Jorge
Abstract This work presents an experimental-numerical design methodology aimed at obtaining a 3D cranial surface from the laser forming of planar sheets. The procedure for determining the laser scanning paths and parameters is presented. First, the laser forming process is characterized via thermomechanical simulation and a strain database, as a function of laser speed and power, is obtained. Then, the strain field required to form the desired shape is determined by flattening the desired surface throughout a numerical simulation where scanning path, laser power, and speed are selected by comparing this strain field against the strain database of the process. Results are analyzed and effectiveness of the approach is experimentally validated.